“Publish or no degree”: Cultivating a scholarly writing Group for Indonesian Master’s students of English education - Fithriani, Rahmah; Ichsanda Rahman Hz, Benni; Seroja br Ginting, Rita (Universitas Islam Negeri Banda Aceh, 2023)
In line with the increasing institutionalization of scholarly publication as a graduation requirement for graduate students around the world, the use of a community of writing practice to support students navigate their publication endeavour has begun to receive attention from academic supervisors and graduate researchers. Despite the burgeoning interest in this topic, there has been little empirical evidence on master’s students’ experiences and perspectives of working within such writing groups at an Indonesian university. This phenomenological case study intends to fill this lacuna by elaborating on the process of a writing group's establishment and development for master's students of English education and exploring their perceptions of participating in such a community of practice (COP). Findings indicate that the writing group served as a flexible and participatory COP that produced critical and enduring alterations in identity as scholarly writers amongst participants. Specifically, their perceived transition into academic writers involves three aspects: knowledge of the values of scholarly publication, construction of a scholarly identity, and demystification of the publishing endeavour. This study's findings can be utilized to inform other master's and doctorate programs, as well as academic professionals seeking interventions to assist their students' productive writing.